Analisis Kebutuhan Bahan Ajar Tematik Tema 2 bagi Siswa Kelas V Sekolah Dasar - Natasya Almuwafiqi; Yuniawatika Yuniawatika; Erif Ahdhianto; Natasya Almuwafiqi; Yuniawatika Yuniawatika (Universitas Negeri Malang, 2023)
Abstract: This study aims to analyze the need for practical and interesting companion teaching materials according to the character of fifth grade elementary school students in order to be able to increase the character of students' curiosity. This study uses descriptive qualitative research methods. The data in this study were obtained from interviews with fifth grade teachers and the distribution of questionnaires to all fifth grade students at SDN Karangsari 2 Blitar City. Based on the results of interviews with fifth grade teachers, it was shown the need for companion teaching materials in theme 2. This is in line with the needs analysis questionnaire showing 78 percent of students need companion teaching materials for theme books. Based on the results of interviews and questionnaires, the needs analysis proves that it is necessary to develop complementary teaching materials for theme 2 thematic books that are integrated with technology to support interactive teaching and learning processes and can increase students' curiosity. Abstrak: Penelitian ini bertujuan untuk menganalisis kebutuhan bahan ajar pendamping yang praktis dan menarik sesuai dengan karakter siswa kelas V SD agar mampu meningkatkan karakter rasa ingin tahu siswa. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Data pada penelitian ini diperoleh dari wawancara dengan guru kelas V serta penyebaran angket kepada seluruh siswa kelas V di SDN Karangsari 2 Kota Blitar. Berdasarkan hasil wawancara dengan guru kelas V SDN Karangsari 2 Kota Blitar menunjukkan perlunya bahan ajar pendamping pada tema 2. Hal tersebut sejalan dengan angket analisis kebutuhan menunjukkan 78 persen siswa perlu bahan ajar pendamping buku tema. Berdasarkan hasil wawancara dan angket analisis kebutuhan membuktikan bahwa perlunya pengembangan bahan ajar pendamping buku tematik tema 2 yang terintegrasi dengan teknologi untuk menunjang proses belajar mengajar yang interaktif dan dapat meningkatkan rasa ingin tahu siswa.